ALTERNATIF STRATEGI PENINGKATAN DAYA SAING SMA KRISTEN 2 SALATIGA - Innes Septa Nindiarini; Bambang Suteng Sulasmono (Universitas Kristen Satya Wacana, 2015)
This research and development aims to formulate strategic plan to enhancing competitiveness in SMA Kristen 2 Salatiga. Data were gathered by means of Focus Group Discussion (FGD), interview, questionnaire, and documentation study. Fishbone analysis is used to identify the root causes of low school competitiveness. The analysis was categorized based on five factors i.e. reputation, school resources, information and technology, human resource, and partnership. Based on the analysis, the strategies are formulated with educational reengineering approach as follows: 1) reconstructing school image by improving academic and non academic achievement, 2) developing innovative curriculum based on outdoor experience and IT, 3) increasing student discipline, 4)optimizing IT usage on promotion and marketing, 5) improving the quality of school programs, 6) developing entrepreneurship programs, 7) improving the quantity and quality school infrastructures, 8) improving teachers’ skill and competence of IT, 9) enhancing the role of school board, 10) maximizing the role of parents, alumnae, and other institution to develop the school programs, and 11) establishing a vocational high school. It is recommended for the school to have cooperation with the stakeholder and the school board to implement the strategic plan so that the competitiveness will enhance in the future.